Reading Walter Benjamin : writing through the catastrophe - Lane, Richard J., 1966- (Manchester University Press : Distributed exclusively in the USA by Palgrave, 2005)
This book explores the persistence of absolute in Benjamin's work by sketching out the relationship between philosophy and theology apparent in his diverse writings, from the early youth movement essays to the later books, essays and fragments. Lane examines Benjamin from two main perspectives: a history-of-ideas approach situating Benjamin in relation to the new German-Jewish thinking at the turn of the twentieth-century, as well as the German youth movements, Surrealism and the "Georgekreis"; and a conceptual approach examining more critical issues in relation to Benjamin and Kant, modern aesthetics and narrative order.